Seasonal litter contribution to total peat respiration from drained tropical peat under mature oil palm plantation - Heru Bagus Pulunggono; Siswanto Siswanto; Husni Mubarok; Happy Widiastuti; Nizam Tambusai; Moh Zulfajrin; Syaiful Anwar; Darmono Taniwiryono; Basuki Sumawinata; Supiandi Sabiham (Brawijaya University, 2022)
The amount of CO2 gas emissions in drained peatland for oil palm cultivation has been widely reported. However, the research addressing the contribution of litter respiration to peat and total respiration and its relationship with several environmental factors is found rare. The aim of this study was to measure peat and heterogeneous litter respiration of drained tropical peat in one year at a distance of 2.25 m and 4.50 m from mature oil palm trees of 14 years using the chamber method (Licor Li-830). In addition to CO2 efflux, we measured other environmental parameters, including peat temperature (10 cm depth), air temperature, groundwater table (GWL), and rainfall. Results showed that the mean total peat respiration (Rt) was 12.06 g CO2 m-2day-1, which consisted of 68% (8.24 g CO2 m-2day-1) peat (Rp) and root (Rr) respiration and 32% (3.84 g CO2 m-2day-1) of litter respiration (Rl) at the distance of 2.25 m from the palm tree. Meanwhile, at a farther distance, the Rt was 12.49 g CO2m-2day-1, the contribution of Rp was 56% (6.78 g CO2 m-2day-1), and Rl was higher than the closest distance (46%; 5.71 g CO2 m-2day-1). Thus, one-year observation resulting the mean Rt and Rr was 0.07–0.08 Mg CO2 ha-1 day-1, while Rl was 0.04–0.06 Mg CO2 ha-1 day-1. The means of Rt, Rp, and Rl were significantly different in the dry season than those recorded in the rainy season. The climatic-related variable such as peat and air temperature were chiefly governing respiration in peat under mature oil palm plantation, whereas the importance of other variables present at particular conditions. This paper provides valuable information concerning respiration in peat, especially for litter contribution and its relationship with environmental factors in peatland, contributing to global CO2 emission.